Deep ice drilling, bedrock coring and dust logging with the Rapid Access Ice Drill (RAID) at Minna Bluff, Antarctica - John W. Goodge; Jeffrey P. Severinghaus; Jay Johnson; Delia Tosi; Ryan Bay (Annals of Glaciology, 2021)
Rapid Access Ice Drill is a new drilling technology capable of quickly accessing the glacial bed of Antarctic ice sheets, retrieving ice core and rock core samples, and providing boreholes for downhole logging of physical properties. Scientific goals include searching for old ice near the glacial bed and sampling subglacial bedrock. During field trials near McMurdo Station on a piedmont glacier at Minna Bluff in the 2019–20 austral summer, we successfully completed a ‘top-to-bottom’ operational sequence in three boreholes by (1) augering through firn, (2) creating a borehole packer seal in non-porous ice, (3) establishing fluid circulation, (4) quickly drilling a borehole in ice at penetration rates up to 1.2 m min−1, (5) acquiring a short ice core at depth, (6) penetrating the glacial bed at a depth of ~677 m, (7) recovering a 3.2 m core of ice, basal till and subglacial bedrock, (8) optically logging the borehole on wireline, (9) testing hydrofracture potential by overpressuring the borehole fluid and (10) operating in an environmentally benign yet rapid field mode. Minna Bluff testing, therefore, demonstrates the effectiveness of this integrated system to drill rapidly through thick ice and penetrate across the glacial bed to take cores of bedrock.